Gender Inclusion Strategies in PNPM - Azarbaijani-Moghaddam, Sippi (World Bank, Jakarta, 2015)
The Program Nasional Pemberdayaan Masyarakat (PNPM) or National Community Empowerment Program is the world’s largest program of its kind with long term goals to reduce poverty by making development planning more inclusive, accountable, and reflective of local needs. PNPM currently covers about 70,000 rural and urban communities across Indonesia. PNPM works by giving communities block grants to spend on projects developed through a participatory, bottom-up planning process, facilitated by social and technical specialists who provide advice to communities without controlling funds. PNPM is supported by a multi-donor trust fund called the PNPM Support Facility (PSF). Part of PSF’s role is to provide more effective strategic support to the government’s objectives, especially by improving the effectiveness of PNPM’s gender action plan. Increasing women’s voice in community planning and decision-making has been an explicit goal of PNPM since its founding, and since 2007 PNPM Rural has had an overarching gender action plan to guide actions to involve women in all procedures. A maximum of 25 per cent of all PNPM funds are reserved to support proposals from village women’s groups for RLF groups referred to in this report as SPP. Women play increasingly central roles in PNPM’s kecamatan and village administration. The PSF engaged a gender specialist with expertise in working in challenging rural contexts to review the system and provide a short critical report and practical recommendation on gender sensitive approaches in the overall implementation of PNPM Rural. A PSF operational analyst with in depth knowledge of PNPM accompanied the specialist to the field. Objectives and outputs are laid out in full in described in Appendix 6. The report below lays out the findings and recommendations of the mission.